2007
DOI: 10.1210/en.2007-0571
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Resistant Insulin-Like Growth Factor (IGF)-Binding Protein-4 Inhibits IGF-I Actions and Neointimal Expansion in a Porcine Model of Neointimal Hyperplasia

Abstract: IGF-I has been shown to play a role in the progression of atherosclerosis in experimental animal models. IGF-binding protein-4 (IGFBP-4) binds to IGF-I and prevents its association with receptors. Overexpression of a protease-resistant form of IGFBP-4 has been shown to inhibit the ability of IGF-I to stimulate normal smooth muscle cell growth in mice. Based on these observations, we prepared a protease-resistant form of IGFBP-4 and infused it into hypercholesterolemic pigs. Infusion of the protease-resistant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…We believe that our approach using a protease-resistant IGFBP4 to block IGF activity is superior to those described above, as it inactivates IGF1, is small enough (24 -32 kDa) to cross the endothelial barrier and should have a long half-life in vivo due its resistance to the PAPP-A protease. In addition to the data presented here, a protease-resistant IGFBP4 was recently shown to inhibit IGF and therefore neointimal expansion in a model of neointimal hyperplasia (Nichols et al, 2007). It is a relatively small molecule compared with antibody therapies, and hence may penetrate tumours more effectively.…”
Section: Discussionmentioning
confidence: 57%
“…We believe that our approach using a protease-resistant IGFBP4 to block IGF activity is superior to those described above, as it inactivates IGF1, is small enough (24 -32 kDa) to cross the endothelial barrier and should have a long half-life in vivo due its resistance to the PAPP-A protease. In addition to the data presented here, a protease-resistant IGFBP4 was recently shown to inhibit IGF and therefore neointimal expansion in a model of neointimal hyperplasia (Nichols et al, 2007). It is a relatively small molecule compared with antibody therapies, and hence may penetrate tumours more effectively.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies (26,36,44,46) have shown that targeted overexpression of IGFBP-4 in transgenic mice resulted in decreased tissue growth. For example, overexpression of IGFBP-4 in osteoblasts reduces bone formation and severely impairs skeletal growth and causes global postnatal growth retardation in mice (43).…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of IGFBP-4 in osteoblasts reduces bone formation and severely impairs skeletal growth and causes global postnatal growth retardation in mice (43). Targeted overexpression of IGFBP-4 in smooth muscle cells led to smooth muscle tissue hypoplasia in transgenic mice and inhibited neointimal expansion in a porcine model of neointimal hyperplasia (26,36,44). Additionally, overexpressing IGFBP-4 using a lymphoid tissue promoter (H-2Kb) decreases thymus growth in transgenic mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…These models attempt to mimic the vascular repair responses to angioplasty, but several important differences must be recognized; for instance, the injury is in general to non-diseased vessels with no pre-existing neointimal cell populations and thus responses come predominantly from proliferating VSMC. Since IGF-1 is a potent VSMC mitogen, the majority of studies exploring mechanical injury models and direct [25,26] or indirect [2730] mechanisms to alter vascular IGF-1 signaling reported that increased IGF-1 or IGF-1 signaling correlates with increased neointimal burden, suggesting that IGF-1 promotes vascular hyperplasia. In particular, targeted overexpression of IGF-1 in VSMC increases neointimal area size [25].…”
Section: Igf-1 and Atherosclerosis Animal Modelsmentioning
confidence: 99%